2016
DOI: 10.1037/lat0000054
|View full text |Cite
|
Sign up to set email alerts
|

Health issues in Hispanic/Latino youth.

Abstract: This review focuses on obesity, asthma and mental health functioning as salient health issues affecting Hispanic youth. Burden of these conditions and consequences for adult health are also discussed. Hispanic youth are affected by obesity at an early age; the prevalence of obesity among Hispanic children 6–11 years old is twice as high as the prevalence for non-Hispanic White children of the same age, but among 2–5 years old is 4 times higher. Asthma disproportionally affects certain Hispanic groups, notably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 122 publications
(172 reference statements)
1
31
0
Order By: Relevance
“…Although some spoke of plans to change their practices, many had vague plans or no plans to reduce the child's weight; most were happy that their child at least was not underweight. This is consistent with previous studies that have shown that Latinx mothers view excess weight as protecting the child from being underweight (Isasi et al, ; Lindsay, Sussner, Greaney, & Peterson, ). One can speculate that cultural norms concerning weight and historical fear of not having sufficient access to food contribute to mother's perception of food and weight, although not explicitly expressed.…”
Section: Discussionsupporting
confidence: 92%
“…Although some spoke of plans to change their practices, many had vague plans or no plans to reduce the child's weight; most were happy that their child at least was not underweight. This is consistent with previous studies that have shown that Latinx mothers view excess weight as protecting the child from being underweight (Isasi et al, ; Lindsay, Sussner, Greaney, & Peterson, ). One can speculate that cultural norms concerning weight and historical fear of not having sufficient access to food contribute to mother's perception of food and weight, although not explicitly expressed.…”
Section: Discussionsupporting
confidence: 92%
“…Children and adolescents with lower social economic status have higher obesity rates, poorer diets, and lower levels of PA [ 7 , 8 , 9 ]. Latino youth are especially at risk for obesity [ 10 ], with significantly higher obesity prevalence (25.8%) than non-Latino youth (11.0–22.0%) [ 1 ]. For Latino youth, obesity rates are high regardless of social economic status [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity rates are highest among Hispanic children and they are at higher risk for obesity-related complications. 16,[34][35][36] Over the past two decades ALL rates have increased in Hispanic children at a greater rate than NH children, [37][38][39] particularly for adolescents aged 15 to 19 years, 37 which is the age group in which our study identified an association of B-ALL diagnosis and obesity among Hispanic youth. Different ethnic groups have different percent body fat with similar BMIs.…”
Section: Discussionmentioning
confidence: 72%